THE BASIS AND CONDITIONS OF PROCEEDINGS IN THE ABSENCE OF THE ACCUSED IN CRIMINAL PROCEEDINGS OF THE REPUBLIC OF ARMENIA - Mkrtchyan, Petik (State and Law, 2022)
The article is dedicated to the basis and conditions of proceedings in the absence of the accused (proceedings in absentia) in the RA criminal proceedings. As a result of the relevant analysis, the author reveals the content of the basis and conditions of remote proceedings in criminal proceedings of the RA and emphasizes the limits of their interpretation in accordance with European standards. The article also presents decisions of the European Court of Human Rights on this issue, and in their light discusses the theoretical problems of interpretation of the grounds and conditions of remote proceedings. In the article an important place is occupied by the study of theoretical problems of production in the absence of the accused, in which the author refers to the interpretation of the basis and content of the conditions of proceedings in absentia. The author reveals what should be understood as evasion from participation in criminal proceedings, and also in which situations it can be said that the accused is properly notified of the criminal prosecution initiated against him. The author also believes that not only practical, but also theoretical issues of proceedings in absentia should be considered in the light of the right to a fair trial in order to correctly understand their essence and make correct assertions.